The coaching dilemma - Franckeiss, Anton (Training and management development methods, 2009)
This paper aims to provoke thought and debate on the nature and quality of executive coaching, and the ability of the industry to offer the specificity and depth that senior managers require. The paper proposes four questions that any business or organization contemplating deploying executive coaching should ask, the answers to which illuminate the real requirement and act as criteria for evaluating services offered by potential suppliers. The paper contends that coaching is in danger of becoming a modern day "snake oil", a treatment whose real worth is misunderstood and which is misapplied as a result. Coaching has significant potential benefits, but an unthinking or casual approach will fail to deliver them, and harm the reputation of a valuable learning and development intervention.